Concurrent validity of Zimbardo Time Perspective Inventory profiles: A secondary analysis of data from the United Kingdom. (18th May 2015) - Worrell, Frank C.; McKay, Michael T.; Andretta, James R.
ABSTRACT: This paper examined the association between membership in profiles based on a shortened form of the Zimbardo Time Perspective Inventory (ZTPI‐S; McKay, Andretta, McGee, & Worrell, 2014) and other temporal and psychosocial variables. Participants consisted of 1620 adolescents attending high school in Northern Ireland. ZTPI‐S scores had correlations with other temporal and psychosocial variables that were similar to those reported for ZTPI scores in previous studies. Four ZTPI‐S profiles were identified—Balanced, Past Negative, Present Hedonistic, and Future—and results indicated that these profiles had theoretically meaningful relationships with self‐esteem, self‐efficacy, aggression, parental attachment, consideration of future consequences, and future temporal focus. Unlike studies of college students where the Balanced profile was related to more adaptive functioning, the Future profile was related to more adaptive functioning. Future studies are needed to establish the generalizability of these profiles and to determine if there are developmental differences in which profiles are more adaptive.